PENERAPAN PEMBELAJARAN COOPERATIVE LEARNING DAN KONVENSIONAL PADA MATERI TRIGONOMETRI DI KELAS X MAN 2 PIDIE JAYA - Arizal Fahmi (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The problem-solving ability of students' mathematics in the field of mathematics studies can be improved if there are approaches in learning, because the approach has an important role in the teaching and learning process. To improve students' mathematical problem-solving abilities, through the cooperative learning model of students' understanding of mathematics on trigonometry material in class X. This study aims to determine whether there is a difference in the mathematical problem-solving abilities of students who study with the cooperative learning approach and the mathematical problem-solving abilities of students who study with conventional approaches (lectures) on trigonometry material in class X. The populations of this study were all students of class X MAN 2 Pidie Jaya which consisted of 60 students consisting of 3 classes. To obtain research data, while the samples in this study were students of class X.1 and X.2 students who were taken randomly. The researcher gave an initial test in the control class and the experimental class to see the students' initial abilities before being taught using the cooperative learning model. Then a final test is given to see if there is an influence on students' ability to solve problems regarding trigonometry. Furthermore, the data obtained in the form of final test results for the control class and the experimental class was analyzed using t-test statistics on the right side. Based on the results of the calculation, the value of tcount < ttable is obtained, namely the price of tcount = 0.521 and the price of ttable = 1.67. So it can be concluded that there is no effect of cooperative learning model on students' mathematical problem solving abilities on trigonometry material in class X MAN 2 Pidie Jaya.